2015
DOI: 10.1007/s11523-015-0364-y
|View full text |Cite|
|
Sign up to set email alerts
|

A combination of the telomerase inhibitor, BIBR1532, and paclitaxel synergistically inhibit cell proliferation in breast cancer cell lines

Abstract: Breast cancer is one of the most significant causes of female cancer death worldwide. Paclitaxel, an extensively used breast cancer chemotherapeutic has limited success due to drug resistance. 2-[(E)-3-naphtalen-2-yl-but-2-enoylamino]-benzoic acid (BIBR1532), a small molecule pharmacological inhibitor of telomerase activity, can inhibit human cancer cell proliferation as well. Thus, to enhance breast cancer treatment efficacy, we studied the combination of BIBR1532 and paclitaxel in breast cancer cell lines. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 52 publications
(67 reference statements)
0
20
0
1
Order By: Relevance
“…Our results also delineated that BIBR1532 augments doxorubicin-induced apoptosis and its antiproliferative effect, as evidenced by the increased externalization of phosphatidylserine (PS), elevated sub-G1 cell population, and decreased number of inhibitor-treated viable cells. Consistently, Shi et al showed that combination of BIBR1532 and paclitaxel synergistically inhibits cell proliferation in breast cancer cell lines [30]. In another study, it was reported that simultaneously treatment of APL-derived NB4 cells with ATO-plus-BIBR1532 resulted in caspase-3 activation and eventually increased apoptotic cell death [31].…”
Section: Discussionmentioning
confidence: 81%
“…Our results also delineated that BIBR1532 augments doxorubicin-induced apoptosis and its antiproliferative effect, as evidenced by the increased externalization of phosphatidylserine (PS), elevated sub-G1 cell population, and decreased number of inhibitor-treated viable cells. Consistently, Shi et al showed that combination of BIBR1532 and paclitaxel synergistically inhibits cell proliferation in breast cancer cell lines [30]. In another study, it was reported that simultaneously treatment of APL-derived NB4 cells with ATO-plus-BIBR1532 resulted in caspase-3 activation and eventually increased apoptotic cell death [31].…”
Section: Discussionmentioning
confidence: 81%
“…Even though previous research report refered to that the clinical efficacy of paclitaxel was affected by drug resistance, in view of its excellent antiproliferation property in the treaty of breast cancer paclitaxel was regarded as one of the effective antiproliferative drugs. 24 At the same time, it has been reported in literatures that both paclitaxel and sirolimus can effectively inhibit neointimal hyperplasia of coronary artery within a month dose range, and the effect has a certain degree of safety. [24][25][26][27] It can effectively reduce the degree of vascular restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…24 At the same time, it has been reported in literatures that both paclitaxel and sirolimus can effectively inhibit neointimal hyperplasia of coronary artery within a month dose range, and the effect has a certain degree of safety. [24][25][26][27] It can effectively reduce the degree of vascular restenosis. Therefore, paclitaxel and sirolimus are commonly used in drug-eluting stents for the treatment of coronary stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Shi et al 17 shows that BIBR1532 inhibited cell proliferation and induced a G1-phase cell cycle arrest in breast cancer cell lines. In this study, the IC 50 values of BIBR1532 were found to be 8.56 and 32 μM at the 72nd hour, respectively.…”
Section: Discussionmentioning
confidence: 99%